Maximum strength and strength training - A relationship to endurance? - Newton, R. U.; Pierce, K. C.; Sands, W. A.; Stone, M. E.; Stone, M. H. (Strength and Conditioning Journal, 2006)
Endurance can be defined as the ability to maintain or to repeat a given force or power output. The sport performance-endurance relationship is a multi-factorial concept.However,evidence indicates that maximum strength is a major component. Conceptually, endurance is a continuum.The literature indicates that (a) maximum strength is moderately to strongly related to endurance capabilities and associated factors, a relationship that is likely stronger for high intensity exercise endurance (HIEE) activities than for low intensity exercise endurance (LIEE); (b) strength training can increase both HIEE and LIEE, the effect being greater for HIEE; (c) the volume of strength training plays a role in endurance adaptation; and (d) mechanical specificity and training program variables also play a role in the degree of adaptation.